Correlation of Depression Symptoms and Interleukin-6 in Chronic Renal Disease with Regular Hemodialysis Patients - Damayanti, Indah; Nasution, Habibah Hanum; Lubis, Wika Hanida (Sumatera Medical Journal, 2018)
Depression is psychosomatic disorder are common in patients with chronic kidney disease (CKD) undergoing hemodialysis (HD). Correlated with morbidity and mortality associated with chronic inflammation in patients, that characterized by elevated levels of plasma cytokines, especially interleukin (IL)-6. Objective: To investigate the correlation of depressive symptoms with IL-6 levels in patients with CKD who underwent regular HD. Methods: One hundred and 29 CKD patients were enrolled in this cross- sectional study. All eligible patients were screened for IL-6 level. Beck Depression Inventory (BDI) II questioner were then given to determine the presence of depression. Level of IL-6 was then correlated with BDI score using Spearman test. Result: The mean BDI score was 19,32 ± 6,18 indicating the level of mild depression symptoms, and the mean IL-6 level (8,697 ± 6,947 pg/mL) was still within normal range. There was a moderate positive correlation (r = 0.417) between the level of depressive symptoms and IL- 6 levels. Conclusion: There was a moderate positive correlation (r = 0.417) between IL-6 levels and depressive symptoms in patient with HD. However, mean IL-6 levels in depressive patients are still within normal limits indicating that the cause of depression is multifactorial.